Analysis of the Effect of Credit Expansion, Operational Efficiency Rate, Lending Interest Rate, NPL of the Previous Period and Capital Adequacy Ratio (CAR) on Non-Performing Loans Based on the Generalized Method of Moment - Dinah Purnamasari; Fatchan Achyani (Yayasan Ahmar Cendekia Indonesia, 2022)
This study aims to determine the effect of credit expansion, operational efficiency, lending interest rate, NPL in the previous period and Capital Adequacy Ratio (CAR) on Non-Performing Loans (NPL). This type of research was quantitative and used secondary data from annual reports. This study used a sample of 20 conventional commercial banks registered on the IDX in 2017-2019 with sample determination using the purposive sampling method. The technique for analyzing data in this study used the Generalized Method of Moment (GMM) with data processing using the help of the Eviews 9 application. Based on the Generalized Method of Moment (GMM) analysis, it was obtained that credit expansion as measured by loan to deposit ratio and lending interest rate did not significantly affect non-performing loans. The level of operational efficiency as measured by Operating Expenses on Operating Income (BOPO), NPL of the previous period, and Capital Adequacy Ratio (CAR) significantly affected non-performing loans.